2013
DOI: 10.1590/1678-7757201302380
|View full text |Cite
|
Sign up to set email alerts
|

Post-curing conversion kinetics as functions of the irradiation time and increment thickness

Abstract: Objective:This study evaluated the variation of conversion degree (DC) in the 12 hours following initial photoactivation of a low-shrinkage composite resin (Venus Diamond).Material and Methods:The conversion degree was monitored for 12 hours using Attenuated Total Reflection (ATR) F-TIR Spectroscopy. The composite was placed in 1 or 2 mm rings and cured for 10 or 20 seconds with a LED lamp. ATR spectra were acquired from the bottom surface of each sample immediately after the initial photoactivation (P=0), 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…15 In an earlier study, Nicola et al concluded that an increased irradiation time produced higher DC at the bottom surface of the restorations. 16 In addition, Gritsch et al explained that a longer exposure time with lower intensities improved the polymerization of the composite in depth. The authors found that this was caused by a delay in the rigid network formation.…”
Section: Discussionmentioning
confidence: 99%
“…15 In an earlier study, Nicola et al concluded that an increased irradiation time produced higher DC at the bottom surface of the restorations. 16 In addition, Gritsch et al explained that a longer exposure time with lower intensities improved the polymerization of the composite in depth. The authors found that this was caused by a delay in the rigid network formation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, suboptimal polymerization of resin composites may promote bacterial colonization at its surface. [ 30 31 32 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…4 For process efficiency and maximum restoration results, more beam-activated composite resins are employed. 5 Currently, quartz tungsten-halogens (QTH) and lightemitting diodes (LED) constitute the light sources most frequently used for hardening composite resin as the photon suppliers which activate photon-initiators. Composite polymerization is initiated by exposure to light produced by a light curing unit (LCU).…”
Section: Introductionmentioning
confidence: 99%
“…8 The DC constitutes an important parameter in determining the final properties of active composite resin irradiation including: physical, mechanical and biological properties the light wavelength and depth employed, ray tip size, photo activation method, distribution, number of inorganic fillers, composite resin color, and the exposure period which is directly affected by an increase in the irradiation period. 5 A low degree of conversion causes decreasing resin properties and the number of non-reactive (trapped or free) residual monomers. One strategy to maximize DC and minimize monomer elution as a means of providing sufficient energy to the material is that of prolonging the hardening time.…”
Section: Introductionmentioning
confidence: 99%